Antitumor activity of polyphenolic extract of Ichnocarpus frutescens - Kumarappan, C.T.; Subhash C. Mandal (Experimental Oncology, 2007)
Aim: Phytochemical and dietary antioxidants are known to decrease the risk of many diseases such as cancer and cardiovascular diseases. In this study polyphenolic extract (PPE) of leaves of Ichnocarpus frutescens was evaluated for antitumor activity in vivo. Materials and Methods: Murine Ehrlich ascites carcinoma (EAC) model was used to assess PPE antitumor activity in vivo. PPE cytotoxicity was determined in vitro in U-937 monocytoid leukemia and K-562 erythroleukemia cell lines. PPE also have been assessed for the free radical scavenging activity against superoxide and nitric oxide radicals. Acute oral toxicity was performed by acute toxic classic method. The total phenolics content was quantified by the Folin-Ciocalteu method. Results: Results of in vivo study showed a significant decrease in tumor volume, viable tumor cell count and a significant increase of life span in the PPE treated group compared to untreated one: the life span of PPE treated animals increased by 53.41% (50 mg PPE/kg) and 73.95% (100 mg PPE/kg). PPE (5, 10 and 20 µg/mL) effectively inhibits in vitro proliferation of U-937 and K-562 cell lines. PPE exhibited pronounced radical scavenging activity with an inhibitory concentration (IC50) value of 167.46 µg/mL and 158.52 µg/mL against superoxide and nitric oxide radicals, respectively. Conclusion: PPE of Ichnocarpus frutescens possesses strong free radical scavenging activity and anti-tumor activity in vitro and in vivo. Цель: исследовать противоопухолевую активность экстракта полифенолов (РРЕ) из листьев Ichnocarpus frutescens на модели
in vivo. Материалы и методы: для анализа противопухолевой активности РРЕ in vivo использовали модель асцитной
карциномы Эрлиха мыши. Цитотоксичность PPE in vitro изучали на клетках моноцитоидной лейкемии линии U-937 и
эритроидной лейкемии линии K Также была проанализирована способность PPE к элиминации свободных радикалов.
Острую токсичность препарата проверяли классическим методом. Общее содержание фенолов определяли методом
Фолина — Чикалто. Результаты: результаты исследования in vivo продемонстрировали значительное уменьшение объема
опухоли, количества живых опухолевых клеток и значительное увеличение продолжительности жизни у животных, получавших
лечение PPE: продолжительность жизни в группах, получавших 50 и 100 мг РРЕ/кг, повысилась на 53,41% и
73,95% соответственно. PPE в концентрациях 5, 10 и 20 µ/мл инибировал in vitro пролиферацию клеток линий U-937 и
K-562. PPE проявил высокую активность к элиминации свободных радикалов с величиной 50 167,46 µг/мл и 158,52 µг/мл
по отношению к супероксид-аниону и оксиду азота. Выводы: PPE из Ichnocarpus frutescens обладает высокой противоопухолевой
активностью in vitro и in vivo.